2011
DOI: 10.1530/eje-11-0134
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-associated polymorphisms are related to insulin resistance and vitamin D deficiency in polycystic ovary syndrome

Abstract: Introduction: Women with polycystic ovary syndrome (PCOS) frequently suffer from metabolic disturbances including insulin resistance (IR), which might be related to vitamin D metabolism. We aimed to investigate the association of polymorphisms in the vitamin D receptor (VDR) gene as well as vitamin D level-associated genes with metabolic and endocrine parameters in PCOS women. Moreover, we examined whether there are associations with PCOS susceptibility. Methods: Metabolic, endocrine, and anthropometric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
152
8
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(185 citation statements)
references
References 35 publications
(46 reference statements)
12
152
8
13
Order By: Relevance
“…We found an about 1.7-fold increased risk of prediabetes and insulin resistance and twofold increased risk of MS and dyslipidaemia in PCOS women with a positive FHx of T2DM. Thus, our findings are consistent with a genetic basis for metabolic disturbances in PCOS, which has been suggested previously (15,25,26). Interestingly, PCOS women with a positive T2DM FHx were more likely to have a positive PCOS FHx suggesting a common genetic background of both diseases.…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
“…We found an about 1.7-fold increased risk of prediabetes and insulin resistance and twofold increased risk of MS and dyslipidaemia in PCOS women with a positive FHx of T2DM. Thus, our findings are consistent with a genetic basis for metabolic disturbances in PCOS, which has been suggested previously (15,25,26). Interestingly, PCOS women with a positive T2DM FHx were more likely to have a positive PCOS FHx suggesting a common genetic background of both diseases.…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
“…Moreover, polymorphisms of the CYP27B1 hydroxylase gene catalyzing the conversion of 25 hydroxyvitamin D 3 (25(OH)D) to its active form were also associated with HT (69). Vitamin D levels were associated with VDR and vitamin D level-related genetic variants (70,71). The latter finding was confirmed by Lin et al (72).…”
Section: The Role Of Vitamin D Deficiencymentioning
confidence: 81%
“…Associations between the low 25(OH)D levels and features of metabolic syndrome (77), and between VDR and vitamin D-related polymorphisms and metabolic and endocrine parameters, but not with PCOS susceptibility per se, have been shown (70). However, in PCOS women from Iran, an association of VDR ApaI polymorphisms with PCOS susceptibility was found (40).…”
Section: The Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…While some studies reported lower levels of vitamin D in women with PCOS [46,47], other studies suggested that levels are comparable [48] or even higher compared to women with PCOS [49]. Several studies have reported an inverse relationship between body mass index (BMI) and vitamin D levels in PCOS patients [50][51][52].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…Wehr et al [46] identified polymorphisms in the VDR gene associated with vitamin D levels in PCOS women, suggesting a role of vitamin D in the pathogenesis of PCOS. In a recent systematic review of 275 publications reporting on the effects of advanced glycation end products (AGEs) on female reproduction, Merhi [54] concluded that AGEs might contribute to the etiology of PCOS and infertility.…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%